Sex, language, and financial inclusion - Francis Osei-Tutu; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Reference to gender in language can lead individuals to draw distinctions between genders and re-inforce traditional views of gender roles. To test our hypothesis that language gender-marking exerts an influence on the gender gap in financial inclusion, we draw on data for 117 countries in the World Bank's Global Findex database and perform logit estimations at the individual level. We find the gender gap in the probability of owning a formal account, having access to a formal credit, as well as having savings in a formal financial institution is higher for countries with gendered languages than for countries with genderless languages. These findings are confirmed in robustness checks that control for alternative measures of culture and estimations at the country level.
URN:NBN:fi:bof-202004032060
Keywords: G21; Z13; 330; financial inclusion; gender; language